PROSTHODONTIC MANAGEMENT OF RESORBED MANDIBULAR RIDGE USING NEUTRAL ZONE IMPRESSION TECHNIQUE: A CASE REPORT - Bhat, Vinaya; Krishna, D Prasad; Kant, Shipra (Journal of Health and Allied Sciences NU, 2015)
One of the most commonly faced problems among long term denture wearers is the reduction in the denture foundation. Prosthetic rehabilitation of a patient with severely resorbed ridge is the most challenging therapy a prosthodontist can undertake. In order to have a favourable prognosis for the denture therapy, impression technique selected should be based on the present state of the basal tissue support. This article presents the application of neutral zone concept being incorporated in impression making to achieve successful complete denture therapy.
Keywords: Neutral Zone Concept; Resorbed Mandibular Ridge; Complete Denture Prosthesis; Functional Moulding Technique